Validation of a Scoring System to Identify Women with Near-Miss Maternal Morbidity - You, Whitney B.; Chandrasekaran, Suchitra; Sullivan, John; Grobman, William (American Journal of Perinatology, 2013)
Objective To validate a five-factor scoring system that identifies parturients who experience near-miss morbidity.Study Design and Setting This study was conducted in an urban, tertiary care hospital over a 2-year period. A narrative case summary was prepared for women with high potential for significant obstetric morbidity. The summary was then reviewed by three physicians, and the extent of morbidity was assigned based on subjective assessment. The same cases were then scored using the proposed five-factor scoring system previously described by Geller et al. Test characteristics of the scoring system were assessed.Results Eight hundred fifteen cases with a high potential for significant morbidity were identified. Subjective review and the scoring system classified 4.5% and 4.2% as near-miss morbidity, respectively, with the scoring system having a corresponding sensitivity of 81.1% (95% confidence interval 64.8 to 92.0%) and a specificity of 99.5% (95% confidence interval 98.7 to 99.9%).Conclusion The scoring system produced similar results to those obtained at its initial development and demonstrated acceptable sensitivity and specificity for identifying near-miss morbidity.
Keywords: near-miss morbidity; maternal mortality; scoring system